'Fostering transformative learning, self-reflexivity and medical citizenship through guided tours of disadvantaged neighborhoods'. Issue 1 (1st January 2018) - Brooks, E. Marshall; Magee, Mary Lee; Ryan, Mark
ABSTRACT: Background and objectives : Medical school curricula increasingly seek to promote medical students' commitment to redressing health disparities, but traditional pedagogical approaches have fallen short of this goal. The objective of this work was to assess the value of using community-based guided tours of disadvantaged neighborhoods to fill this gap. Methods: A total of 50 second-year medical students participated in a guided tour of disadvantaged public housing neighborhoods in Richmond, Virginia. Students completed self-reflexive writing exercises during a post-tour debriefing session. Student writings were analyzed to assess the tour's effect on their awareness of poverty's impact on vulnerable populations' health and wellbeing, and their personal reactions to the tour. Results: Student writings indicated that the activity fostered transformative learning experiences around the issue of poverty and its effects on health and stimulated a personal commitment to working with underserved populations. Themes from qualitative analysis included: increased awareness of the extent of poverty, enhanced self-reflexive attitude towards personal feelings, biases and misperceptions concerning the poor, increased intentional awareness of the effects of poverty on patient health and well-being, and, encouragement to pursue careers of medical service. Conclusions: This pilot demonstrated that incorporating self-reflexive learning exercises into a brief community-based guided tour can enhance the social consciousness of medical students by deepening understandings of health disparities and promoting transformative learning experiences.